STREAM–an energy scenario modelling tool. (August 2018) - Bramstoft, Rasmus; Pizarro Alonso, Amalia; Karlsson, Kenneth; Kofoed-Wiuff, Anders; Münster, Marie
Abstract: Energy system models are powerful tools used to develop decarbonisation pathways and to assess the green energy transition. This paper presents the open source energy scenario tool STREAM, by describing the modelling approach, applications, strengths, limitations, and potential future developments. STREAM is a dialogue tool, which is used by a broad audience to conduct quick analyses and to explore plausible scenarios for future integrated energy systems, covering all sectors. STREAM is a relatively simple spreadsheet, which ensures transparency, allows stakeholder involvement, and is suitable for scenario discussions and developments. Moreover, STREAM can be soft-linked with more sophisticated energy tools. STREAM contributes to the integrated energy systems modelling field by providing a fast transparent open source modelling tool, which simulates the entire energy system with detailed chronological temporal resolution, in order to provide insights related to future energy trends. Results from the STREAM model are used by researchers, stakeholders, and policy makers in developing scenarios for analysing strategic decisions regarding the desired development of future energy systems. Highlights: STREAM is a scenario development tool for energy transition and decarbonisation pathways. STREAM simulates the entire energy system, including electricity, heat and transportation. STREAM facilitates transparency, stakeholder involvement, and quick system assessments. STREAM is an open source and open code energy systems model built in spreadsheets.